ENDOCRINE EVENTS AND LIFE STAGES OF WOMEN - Khan, Mir Hassan; Khan, Jahangir A.; Idrees, Mohammad (Journal of Ayub Medical College Abbottabad, 1998)
The sex of every baby is determined at the time of conception1. If a "Y" carrying sperm fertilizes an ovum, the sex of the developing fetus will be male. If the ovum is fertilized by a sperm carrying X chromosome, the result will be a female embryo. On each side of the embryo, a primitive gonad arises from the genital ridge2. The gonad develops a cortex and a medulla. Until the sixth week of development, these structures are identical in both sexes. In case of XY chromosomes, the medulla develops into a testis during the 7-8 weeks and the cortex regresses1. Leydig cells appear next and small amount of testosterone is secreted for growing male sex organs of fetus2. While in case of XX chromosomes, the cortex develops into an ovary and the medulla regresses. The embryonic ovary does not secrete hormones. Each of the embryonic ovaries is initially populated by about 1000 to 2000 primordial germ cells which through rapid proliferation give rise in each ovary to about three million oocytes1. This number of oocyte is reduced through cell death to 1 million at birth and each of them is surrounded by a single layer of flattened epithelial cells, granulosa cells. The ovum remains inactive and is suspended in the prophase stage of meiotic division till puberty1. After puberty in response to GnRH from hypothalamic pituitary glands produce gonadotrophic hormones. The responsibility of imprinting the fetal hypothalamus to produce a male or female pattern of gonadotrophin release has been ascribed to testosterone